Obstructive Sleep Apnea and Gastroesophageal Reflux: A Multivariate Population‐Level Analysis. (8th December 2015) - Gilani, Sapideh; Quan, Stuart F.; Pynnonen, Melissa A.; Shin, Jennifer J.
Abstract : Objectives: Previous studies investigating the relationship between gastroesophageal reflux (GER) and obstructive sleep apnea (OSA) demonstrate mixed results and have had limited capacity to control for concurrent confounders. Our objectives were to (1) determine if GER is significantly associated with OSA when simultaneously adjusting for the presence of other potentially confounding conditions and (2) quantify the magnitude of any such association that exists. Study Design: Cross‐sectional analysis of the National Ambulatory Medical Care Survey and National Hospital Ambulatory Medical Care Survey, 2005‐2010. Setting: Ambulatory visits in the United States. Subjects and Methods: Adults with a diagnosis of OSA or GER and potentially confounding conditions were identified. Univariate and multivariate logistic regression analyses were performed, as well as sensitivity analyses based on increasingly narrow diagnostic definitions. Results: A significant positive association between GER and OSA was observed, which persisted after adjustment for age, sex, race/ethnicity, sinonasal obstructive and inflammatory disorders, laryngopharyngeal obstructive and inflammatory disorders, obesity, asthma, and lung disorders. This positive association remained significant regardless of diagnostic criteria, whether broad (odds ratio: 1.94, 95% confidence interval: 1.07‐3.54, P =. 030) or narrow (odds ratio: 2.13, 95% confidence interval: 1.17‐3.88, P =. 014). Conclusion: In this analysis of a national database defining the 3 most prioritized diagnoses, GER is independently associated with OSA, with double the odds of concurrent occurrence, even while controlling for potentially related conditions.